2015
DOI: 10.1111/1750-3841.13078
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis and Flavor Characteristics of Serrano Ham Processed under Different Ripening Temperature Conditions

Abstract: Medium and high ripening temperature conditions (RTC) may be applied to Serrano ham in order to enhance the phenomena associated with ripening, without loss of product quality. Moisture loss, degradation of proteins and formation of free amino acids were accelerated in medium and high RTC hams. From month 5 to month 9 of ripening, development of a high quality flavor evolved more rapidly in medium RTC hams, flavor intensity increased at a faster rate in high RTC hams, and raw-meat taste declined more rapidly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Afterwards, hams were ripened at low, medium or high RTC, with respective average temperatures of 9.3, 14.3 and 19.1°C. Thermal integral (Σ T Á t) values of low, medium and high RTC hams were 154, 220 and 286°C month, respectively, and NaCl concentrations 3.79%, 4.32% and 5.30% (w/w), respectively, at the end of the ripening period (del Olmo et al, 2015).…”
Section: Ham Processing and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterwards, hams were ripened at low, medium or high RTC, with respective average temperatures of 9.3, 14.3 and 19.1°C. Thermal integral (Σ T Á t) values of low, medium and high RTC hams were 154, 220 and 286°C month, respectively, and NaCl concentrations 3.79%, 4.32% and 5.30% (w/w), respectively, at the end of the ripening period (del Olmo et al, 2015).…”
Section: Ham Processing and Samplingmentioning
confidence: 99%
“…Regarding the influence of RTC on ham texture (pooled data from four muscles and five ripening times), cutting force reached the highest value (42.49 N) in high RTC hams and the lowest (38.90 N) in medium RTC hams; cutting energy the highest value (0.43 J) in high RTC hams and the lowest (0.39 N) in low RTC hams; shear force the highest value (374 N) in medium RTC hams and the lowest (310 N) in low RTC hams; and shear energy the highest value (2.42 J) in high RTC hams and the lowest (1.81 J) in low RTC hams. The effect of RTC on ham texture may be partly ascribed to the effect of temperature and relative humidity of the air in the ripening chamber on the water content of ham (Serra et al, 2005), resulting in lower water content at the higher RTC (del Olmo et al, 2015). The differences in protein degradation between hams ripened under various RTC, with enhanced proteolysis at higher temperatures (del Olmo et al, 2015), can be also responsible for the observed differences in texture.…”
Section: Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have been focused on non-volatile compounds of the meat products, including dry-cured hams [3,4] and fermented sausages [5,6]. All these researches indicated that a number of complex chemical and biochemical reactions occur during processing meat products: muscle proteins break down into small peptides and free amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The flavor of dry‐cured hams is one of the most important quality attributes affecting the acceptability of consumers . Lipolysis‐oxidation played a very important role on the flavor of Jinhua hams during the ripening period .…”
Section: Introductionmentioning
confidence: 99%